Analisis Manajemen Sarana dan Prasarana di Sekolah Dasar - Citra Anugrahwati; Dini Rosyada Mahmud; Erwin Simon Paulus Olak Wuwur; Citra Anugrahwati; Dini Rosyada Mahmud (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: The sarpras component is part of the school system and part of school accreditation. The existence of infrastructure management can support learning in schools to be effective and efficient. The type of research used is descriptive qualitative with the aim of exploring information data related to the benefits and maintenance of infrastructure facilities in elementary schools. The subjects used in this research were school principals, infrastructure managers, educators, and students. As for data collection techniques obtained by observation, in-depth interviews, and documentation. In addition, researchers analyze data using steps such as reducing data, displaying data, and drawing conclusions. From the needs analysis and self-assessment conducted at SD Harapan Bangsa Trilingual Elementary School, there are facilities such as: Adequate shelves/storage cabinets. books, textbooks, and props. As well as the process of analysis and evaluation of facilities and infrastructure that has been carefully thought out so that the facilities and infrastructure at the SD are good. All school members must carry out maintenance work to keep the facilities and infrastructure in good condition so that they can be used by teachers and students. Abstrak: Komponen sarpras yaitu bagian dari sistem di sekolah dan bagian dari akreditasi sekolah. Adanya manajemen sarpras dapat menunjang pembelajaran di sekolah menjadi efektif dan efisien. Jenis penelitian yang digunakan yaitu kualitatif deskriptif memiliki tujuan untuk menggali data informasi terkait manfaat dan perawatan sarpras pada sekolah dasar. Subjek yang digunakan penelitian yaitu kepala sekolah, pengelola sarpras, pendidik, peserta didik. Adapun teknik pengumpulan data diperoleh observasi, wawancara mendalam, serta dokumentasi. Selain itu, peneliti menganalisis data menggunakan langkah-langkah seperti merreduksi data, mendisplay data, serta menarik kesimpulan. Dari analisis kebutuhan dan penilaian diri SD Harapan Bangsa Tribahasa yang dilakukan terdapat fasilitas seperti: Rak/lemari penyimpanan yang memadai. buku, buku teks, dan alat peraga. Serta adanya proses analisis dan evaluasi sarana dan prasarana telah dipikirkan dengan matang sehingga sarana dan prasana di SD tersebut telah baik. Semua warga sekolah harus melakukan pekerjaan pemeliharaan untuk menjaga sarana dan prasarana dalam kondisi baik agar dapat digunakan untuk guru dan siswa.